PENENTUAN STRATEGI PENGEMBANGAN USAHA KERAJINAN PELEPAH PISANG DI KECAMATAN WRINGINANOM GRESIK - Andri Krisna Dianto, Andri Krisna Dianto (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2019)
The development of the number of small industrial businesses in Wringinanom Gresik is increasing. One of them is the banana midrib rope craft industry. This study aims to determine the condition of banana fronds business, internal and external factors of banana midrib woven business, alternative strategies and priority strategies applied in developing banana midrib woven business in Mondoluku Village, Sooko, Kesambenkulon, Sumbergede, Wringinanom District, Gresik. The sample is 42 entrepreneurs. The variables of this study are labor, capital, marketing, and raw materials. The method of data collection includes interviews and documentation, this study uses descriptive methods. The data used are primary and secondary. Analysis of the data used are (1) IFE Matrix and EFE Matrix, (2) IE Matrix, (3) SWOT Matrix, (4) QSP Matrix. The results showed that the management of the banana midrib rope business in Wringinanom District was less than optimal. IE matrix values ​​of 2.414 on IFE total weight and 2,979 on EFE total weight indicate this business position in Cell V maintaining and maintaining (hold and maintain). The SWOT matrix generates several alternative strategies which will be determined by the QSP matrix. The highest TAS (Total Attractive Score) value in the QSP matrix is ​​5.629, which is the priority strategy to increase production capacity and product quality that has been made to maintain consumer confidence. The most effective development strategy priority that can be applied to the banana midrib rope business in Wringinanom District is to increase production capacity and product quality that has been made to maintain consumer confidence.